A smart mirror to promote a healthy lifestyle. (October 2015) - Colantonio, Sara; Coppini, Giuseppe; Germanese, Danila; Giorgi, Daniela; Magrini, Massimo; Marraccini, Paolo; Martinelli, Massimo; Morales, Maria Aurora; Pascali, Maria Antonietta; Raccichini, Giovanni; Righi, Marco; Salvetti, Ovidio
Abstract : ICT solutions to foster behavioural change have been shown to be effective in implementing primary prevention in terms of a healthy lifestyle. Primary prevention is the most viable approach to reduce the socio-economic burden of chronic and widespread diseases, such as cardiovascular and metabolic diseases. In this paper, we present a novel multisensory device, the Wize Mirror, which is under development in the EU FP7 Project SEMEOTICONS. The Wize Mirror detects and monitors over time semeiotic face signs related to cardio-metabolic risk, and encourages users to reduce their risk by improving their lifestyle. Highlights: Wize Mirror seeks to move semeiotic analysis of the face to normal life settings. The goal is to promote primary prevention of cardio-metabolic diseases. Wize Mirror will support people in self-monitoring and self-assessing wellbeing. It is non-intrusive, interacts natural with user, and gives tailored guidance. The guidance will give with coaching and ensure awareness and comprehension.